SOCIAL STRATEGY PADA MEDIA SOSIAL UNTUK PROMOSI PARIWISATA DAERAH ISTIMEWA YOGYAKARTA - Zahrotul Umami (Master of Communication Science Program, Universitas Diponegoro, 2015)
ABSTRACT:This study was done to see a communications strategy using social strategy to conduct a tourismpromotion by establishing a relationship between tourism stakeholders with the customer in this casetourists. Social strategy through social impact and impact strategy facilitates the use of social mediaas a tool of promotion in today's digital era.This study used a qualitative approach with in-depth interview to the perpetrators of tourism inYogyakarta. The results showed that the Social Strategy through social impact and impact strategyfor the promotion of tourism in Yogyakarta can build a relationship between tourism stakeholderswith tourists both online and offline. Promotional activities can easily provide awareness and can betransmitted by social media followers to users of other social media